Monuments, marks and tributes: the last dictatorship, the uses of the past and the construction of self-legitimating narratives (Buenos Aires, 1979-1980) (Quinto Sol, 2020)
The issue concerning repressive control and the conquest of social consensus is disturbing scholars of the fascist and authoritarian regimes. In Argentina, a group of researchers stated that culture had a strategic place in the dictatorial project. Since then there have been a series of discussions in which this work is inscribed.Our work studies the ways in which in the public space materialized the official dictatorial self-legitimization discourse presented with the purpose of convincing the population that the Armed Forces were the indicated ones to establish a new social "order". To do this, we set out to register a series of facilities or markings (monuments, plaques, etc.) as well as cultural practices such as the declaration of commemoration days, opening of museums, etc. We have classified these official interventions according to two central objectives: a- the vindication of a military tradition with which to compose the image of a venerable Army; and b- the sacrificial recognition of the military "fallen" in combat against the enemy of the country.
Keywords: dictatorship; culture; monuments; tributes